2022
DOI: 10.1002/prp2.995
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of functional and radioligand binding characteristics of GPER ligands confirming aldosterone as a GPER agonist

Abstract: Aldosterone exerts some of its effects not by binding to mineralocorticoid receptors, but rather by acting via G protein‐coupled estrogen receptors (GPER). To determine if aldosterone binds directly to GPER, we studied the ability of aldosterone to compete for the binding of [3H] 2‐methoxyestradiol ([3H] 2‐ME), a high potency GPER‐selective agonist. We used GPER gene transfer to engineer Sf9‐cultured insect cells to express GPER. We chose insect cells to avoid interactions with any intrinsic mammalian receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…It should be noted that a significant reduction in heart rate and increases in stroke volume occurred in aldosterone-treated rats even on the low-salt diet, that is, before initiation of salt-induced elevations in blood pressure. The heart rate changes are consistent with studies showing that aldosterone binds to GPERs (G-protein–coupled estrogen receptors) 39 and decreases heart rate by activating GPER in cardiac vagal neurons of nucleus ambiguus. 40 Other investigators using continuous telemetry recordings have shown similar reductions in heart rate during initiation of hypertension induced by deoxycorticosterone (DOC) and salt.…”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that a significant reduction in heart rate and increases in stroke volume occurred in aldosterone-treated rats even on the low-salt diet, that is, before initiation of salt-induced elevations in blood pressure. The heart rate changes are consistent with studies showing that aldosterone binds to GPERs (G-protein–coupled estrogen receptors) 39 and decreases heart rate by activating GPER in cardiac vagal neurons of nucleus ambiguus. 40 Other investigators using continuous telemetry recordings have shown similar reductions in heart rate during initiation of hypertension induced by deoxycorticosterone (DOC) and salt.…”
Section: Discussionsupporting
confidence: 88%
“…Unexpectedly, accumulating evidence is revealing that, in addition to MR, aldosterone can bind to GPER to exert its non-genomic actions ( 9 , 18 , 19 ). Furthermore, Ang II can influence aldosterone synthesis through the interaction of Ang II receptor type 1 with GPER (8), providing a mechanism to link GPER overexpression with the elevation in aldosterone in patients with aldosterone-producing adenomas.…”
Section: Hypertension and Aldosteronementioning
confidence: 99%
“…A subsequent study showed that GPER can interact with aldosterone and mediate non-genomic pathways in a manner distinct from the classic MR-mediated activation mechanism. A recent study suggested that the GPER-dependent effects of aldosterone likely occur by direct binding, with a stronger binding potency of GPER to aldosterone than to estrogen; however, the binding of GPER is the strongest to [ 3 H] 2‐ME, a high-potency GPER-selective agonist in insect cells without any of the intrinsic mammalian receptors for aldosterone ( 19 ).…”
Section: Gper: a New Receptor For Aldosteronementioning
confidence: 99%
“…Despite accumulating evidence for aldosterone’s actions through GPER, there remains significant speculation that aldosterone directly binds to GPER [ 97 , 98 , 99 ]. However, a recent work has demonstrated a direct interaction of aldosterone with GPER through the data showing that aldosterone competitively binds GPER with other GPER ligands [ 100 ]. Meanwhile, in a reperfusion injury study of the heart, using a polymer analogue of aldosterone to selectively activate the non-genomic receptors of aldosterone, it was found that the GPER antagonist G-36 but not spironolactone, a MR blocker, could block the action of aldosterone [ 101 ].…”
Section: Tissue Cellular Localization Ligands and Classical Signaling...mentioning
confidence: 99%